Ultrasonographic evaluation of cervical length and amniotic fluid index as predictor of pregnancy outcome in case of preterm premature rupture of membrane - Patil, Prashant; Kumari, Archana; Anand, H. P. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Preterm premature rupture of membrane (PPROM) is among the most important cause of the perinatal morbidity and mortality. We sought to determine whether cervical length and amniotic fluid index individually or in combination can predict the pregnancy outcome in cases of PPROM. Methods: The prospective observational study was done on 170 women complicated by PPROM with gestational age between 24-36+6 weeks. They were categorized into three groups Group I.24-28 weeks, Group II.28+1 to 32 weeks and Group III. 32+1 to 36+6 weeks. Cervical length and amniotic fluid index were measured using trans abdominal ultrasound within 24 hr of admission. Maternal outcomes were recorded in terms of latency period, chorioamnionitis, and abruption , and neonatal outcomes were recorded in terms of birth weight, first minute APGAR score <7, NICU admission and early neonatal death. Qualitative variables were correlated using Chi-Square test /Fisher’s exact test. Univariate logistic regression was used to assess cervical length and AFI as a predictor of complication. A p value of <0.05 was considered statistically significant. Results: Out of 170, majority (95) belonged to 28+1 to 32 weeks group. Latency was inversely related to period of gestation (p<0.0001). A long cervical length correlated with increased latency, increased risk of chorioamnionitis and increased neonatal complications in all three groups. Also, women with PPROM having AFI >5 cm had a greater mean latency period (8.32±1.25 days) which increased their risk of developing chorioamnionitis as compared to women with PPROM having AFI ≤5 cm, who had a shorter mean latency period (7.63±1.07 days) and a lower risk of developing chorioamnionitis (p value <0.0001). Conclusions: Latency is inversely related to period of gestation. A long cervical length and increased amount of AFI correlates with increased latency, increased risk of chorioamnionitis and increased neonatal complications.